Mayday! Mayday! What Critical Communication Skills Are Needed For Young Aviators? - Aina Suriani Mahmood; Noor Saazai Mat Saad; Nurhayati Mohd Nur (Research Energy Foundation, 2024)
Non-Indexed Publication